Marketing Practices for Competitiveness in Public Further Education and Training Colleges in Gauteng - Fadahunsi, Tayo; Pelser, Theuns (South African Journal of Higher Education, 2016)
Marketing is now regarded as an essential set of principles and practices which are necessary to attract and retain customers. Colleges and other service providers are faced with competitive situations where it is necessary to satisfactorily meet the needs of the customers and to have competitive advantage that will ensure long term survival. Unfortunately, there is inadequate knowledge on the application of marketing practices for competitiveness in public further education and training (FET) colleges in South Africa. It was thus necessary to look into the marketing practices that are being used for competitiveness by public FET colleges in Gauteng. A survey was undertaken to describe the current state of affairs in colleges in Gauteng with respect to the marketing practices being used to ensure competitiveness. The survey was conducted making use of a questionnaire, with a sample size of 250. The relevant findings about the respondents indicate that, they were positive about marketing practices used by their colleges for competitiveness, but they need to understand the practices of marketing better for increasing competitiveness in their respective colleges.